2014
DOI: 10.4103/0253-7613.129301
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ketamine against hemorrhagic cystitis in rats receiving ifosfamide

Abstract: Objective:To investigate the possible protective effect of a single dose of ketamine and the synergistic effect between ketamine and 2-mercaptoethane sulfonate (mesna) against ifosfamide-induced hemorrhagic cystitis.Materials and Methods:35 adult female wistar rats were divided into five groups and pretreated with ketamine at 10 mg/kg and/or mesna 400 mg/kg 30 minutes before intraperitoneal injection of IFS (400 mg/kg) or with saline (control group). Hemorrhagic cystitis was evaluated 24 hours after IFS inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…This result suggested that IFS (or CTX) and ketamine have opposing effects on the urinary bladder, probably due to their different effects on iNOS activities. In the present study, the results observed in the ketamine-treated SMCs are consistent with the results of previous studies, which suggested that the production of proinflammatory mediators, such as IL-6 and free oxygen radicals (nitric oxide), are reduced in SMCs following ketamine treatment ( 60 , 62 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result suggested that IFS (or CTX) and ketamine have opposing effects on the urinary bladder, probably due to their different effects on iNOS activities. In the present study, the results observed in the ketamine-treated SMCs are consistent with the results of previous studies, which suggested that the production of proinflammatory mediators, such as IL-6 and free oxygen radicals (nitric oxide), are reduced in SMCs following ketamine treatment ( 60 , 62 ).…”
Section: Discussionsupporting
confidence: 93%
“…Following administration of CTX, iNOS bladder activity increases, which is associated with histopathological alterations ( 61 ). Ozguven et al reported that appropriate ketamine pretreatment attenuated experimental IFS-induced hemorrhagic cystitis in a rat model ( 62 ). This result suggested that IFS (or CTX) and ketamine have opposing effects on the urinary bladder, probably due to their different effects on iNOS activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe any change of detrusor relaxation or bladder compliance in stressed mice (Figure 5), which was in line with the results by Mingin et al, 3 Short‐term (28 days) ketamine (25 mg/kg/day) treatment could induce bladder overactivity and ketamine‐induced cystitis in female rats 10,11 . But single low dose of ketamine pretreatment attenuates experimental ifosfamide‐induced bladder damage 12 . In our current study, single dose of ketamine treatment did not induce bladder overactivity (Figure 3), and short‐term (5 days) ketamine (25 mg/kg/day) is not associated with more intensity of SS‐induced detrusor overactivity.…”
Section: Discussionsupporting
confidence: 91%
“…10,11 But single low dose of ketamine pretreatment attenuates experimental ifosfamideinduced bladder damage. 12 In our current study, single dose of ketamine treatment did not induce bladder overactivity (Figure 3), and short-term (5 days) ketamine (25 mg/kg/day) is not associated with more intensity of SS-induced detrusor overactivity. The results also showed that short-term (1 or 5 days) ketamine did not improve detrusor overactivity and impaired contractility as evidence by no altered urine BDNF level in ketaminetreated SS 1 mice when compared with SS 1 K 0 .…”
Section: Discussionsupporting
confidence: 46%
“…According to literature data, IF administered in a larger single dose (400 – 500 mg/kg b.w.) exerts an intensified nephrotoxic effect, manifested with Fanconi syndrome [15,16]. Moreover, the choice of the applied IF dose was also consistent with the clinical data.…”
Section: Methodssupporting
confidence: 55%